Salinity study of irrigation waters used in rice fields - Martins Júnior, Marcos Cardoso; Poletto, Naracelis (Revista de Ciências Agroveterinárias, 2022)
In Santa Catarina State, Brazil, rice is predominantly cultivated in irrigated systems, and irrigation water is generally collected directly from watercourses. Irrigated rice crops, which are sensitive to water salinity, form the basis of the economy of the Mampituba River Basin region, southern Brazil. This study aimed to assess salinity fluctuations in waters collected from the Mampituba River for irrigation of rice crops during the four seasons of the year. For salinity determination, water samples were collected from six sites along the river course, from the source to the mouth. Three subsamples were collected at each site, with a mean interval of 15 days between collections, beginning in May 2016 and ending in April 2017. Samples were evaluated for electrical conductivity (EC). Assessment of salinity damage was performed in seedlings of rice cultivars ‘IRGA 417’ and ‘EPAGRI 106’. When seedlings reached the S2 stage, they were transplanted into flooded soil at different saline concentrations. EC values ranged from 224 to 20,120 µS cm−1 over the experimental period, being higher at sites closer to the sea. The highest salinity values were recorded between November 2016 and January 2017. It was possible to observe an inverse relationship between rainfall and water salinity. Salinity causes damage to rice plants, particularly seedlings. Symptoms include leaf tip chlorosis, leaf curling, and necrosis of old leaves. It is important for rice farmers to understand salt wedge fluctuations within their estuary as well as variations in salinity levels at different sites and times of the year.